2009
DOI: 10.1124/jpet.109.160093
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Ampicillin Elevates Hepatic Primary Bile Acid Synthesis through Suppression of Ileal Fibroblast Growth Factor 15 Expression

Abstract: Administration of the antibacterial drug ampicillin (ABPC) significantly increased hepatic bile acid concentrations. In the present study, we investigated the mechanisms for the elevation of bile acid levels in ABPC-treated mice. Hepatic microsomal cholesterol 7␣-hydroxylation and CYP7A1 mRNA level were increased 2.0-fold in ABPC-treated mice despite higher bile acid levels in the liver and small intestinal lumen. A significant change in hepatic small heterodimer partner (SHP) mRNA level was not observed in AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 41 publications
(42 reference statements)
2
49
0
1
Order By: Relevance
“…4,5) Ampicillin (ABPC) treatment increases the bile acid pool size and hepatic bile acid concentration in experimental animals. 6) This disruption of bile acid homeostasis is in part due to the elevation of bile acid synthesis. The mRNA levels of hepatic rate-limiting enzyme in bile acid synthesis, Cyp7a1, and hepatic cholesterol 7α-hydroxylase activities are increased in mice treated with antibacterial drugs.…”
mentioning
confidence: 99%
“…4,5) Ampicillin (ABPC) treatment increases the bile acid pool size and hepatic bile acid concentration in experimental animals. 6) This disruption of bile acid homeostasis is in part due to the elevation of bile acid synthesis. The mRNA levels of hepatic rate-limiting enzyme in bile acid synthesis, Cyp7a1, and hepatic cholesterol 7α-hydroxylase activities are increased in mice treated with antibacterial drugs.…”
mentioning
confidence: 99%
“…Fxr-null mice, lacking FXR signaling, show lower expression levels of intestinal Fgf15 and hepatic Shp mRNA. 17,18) Therefore, not only the lack of direct FXR signaling but also the attenuation of FGF15-and SHP-mediated signaling contributes to the elevation of the hepatic lipid levels in Fxr-null mice. However, whether FGF15/19 signaling compensates for the lack of FXR signaling that regulates hepatic lipogenesis remains unknown.…”
mentioning
confidence: 99%
“…15,16) FGF15/19 has been reported to down-regulate the hepatic expression of CYP7A1 to reduce bile acid synthesis. 8,16,17) Studies using FGF19-transgenic mice and FGF19-treated hyperlipidemic mice have indicated that FGF19 also regulates the hepatic levels of lipids, such as triglyceride (TG) and cholesterol. 7,9) However, how the FGF15/19-FGFR4 signal controls the hepatic lipid levels remains unclear.…”
mentioning
confidence: 99%
“…Previous studies elucidated that FGF15/19 suppresses ASBT which modulates intestinal BA re-absorption in enterocytes and cholangiocytes (Li et al, 2005;Sinha et al, 2008). Moreover, AMP-treated mice have less BA in feces, more BA in portal blood, and elevated levels of ASBT in ileum (Miyata et al, 2009). Interestingly, a decrease in ASBT in ileum was observed when AMP-treated mice were administered T-DCA or CA (Miyata et al, 2011).…”
Section: Transportation Of Bas Regulated By Intestinal Microbiotamentioning
confidence: 91%
“…Administration of antibiotic, such as AMP, bacitracin, streptomycin, and neomycin, can elevate hepatic BA biosynthesis in the liver via suppression of FGF15 expression in ileum, indicating that less FXR is activated by BA (Miyata et al, 2009). Previous research has revealed that compared with GF mice, conventionally raised (CONV-R) mice had decreased T-β-MCA and elevated T-CA.…”
Section: Biosynthesis Of Bas Regulated By Intestinal Microbiotamentioning
confidence: 99%